Literasi Digital dalam Menanggulangi Perundungan Siber di Dunia Olahraga - Jufadli Rachmad; Yadi Supriadi (Bandung Conference Series: Journalism, 2023)
Abstract. As a celebrity in sports, athletes usually use social media to maintain relationships with their fans. But it's not uncommon for an athlete to experience bullying, not infrequently social media accounts belonging to athletes and football clubs are flooded with scathing comments and even insults. This insult has a negative impact on the mentality and performance of athletes and the perpetrators of bullying themselves so that education regarding digital literacy related to cyberbullying in the world of sports is something that is considered important. As one of the teams with the largest supporter base in Indonesia, Persib's management and players' social media accounts are certainly not free from criticism. Some of these criticisms even lead to cyberbullying. The research discusses digital literacy efforts carried out by the Persib Bandung football club regarding cases of cyber bullying in the world of sports. The research was conducted using a case study analysis approach by interviewing a number of sources, namely Persib's Creative Director, Persib’s Head of Communication, Persib's Content Manajer, and Persib's Vice President of Commercial. The research results show that the digital literacy efforts carried out by Persib Media are influenced by various pressures and negative comments received by the club, based on Persib's vision in shaping the mentality of its supporters, as well as the view that Persib is a platform that can be used to educate and build society. through character development. Abstrak. Sebagai seorang selebritas di bidang olahraga, atlet biasanya menggunakan media sosial untuk menjaga hubungan dengan para penggemarnya. Namun tak jarang seorang atlet mengalami perundungan, tak jarang akun media sosial milik atlet maupun klub sepak bola dibanjiri oleh komentar-komentar pedas bahkan cacian. Cacian tersebut berdampak buruk pada mental hingga performa atlet maupun pelaku perundungan itu sendiri sehingga adanya edukasi mengenai literasi digital terkait perundungan siber di dunia olahraga menjadi hal yang dirasa penting. Sebagai salah satu tim dengan basis supporter terbesar di Indonesia, akun media sosial milik manajemen maupun para pemain Persib tentunya tak terlepas dari kritikan. Beberapa dari kritikan tersebut bahkan mengarah pada perundungan siber. Penelitian membahas terkait upaya literasi digital yang dilakukan oleh klub sepak bola Persib Bandung terkait kasus perundungan siber di dunia olahraga. Penelitian dilakukan menggunakan pendekatan analisis studi kasus dengan mewawancarai sejumlah narasumber yakni Creative Director Media Persib, Head of Communication Persib, Content Manajer Media Persib, dan Vice President Commercial Persib. Hasil Penelitian menunjukan bahwa upaya literasi digital yang dilakukan Media Persib dipengaruhi oleh berbagai tekanan dan komentar negatif yang diterima oleh klub, didasari oleh visi Persib dalam membentuk mental suporternya, serta pandangan bahwa Persib sebagai platform yang dapat digunakan untuk yang dapat digunakan untuk mengedukasi serta membangun masyarakat melalui pembangunan karakter.